Transformation of Inspirational Population Administration Services in Biringkanaya District - Djohar Djohar; Susanty I Mutia Shadat; Dety Junita Sulanjari; Umar Kamaruddin; Ahmad Syaekhu (Program Pascasarjana Universitas Negeri Makassar, 2023)
This research aims to analyze the factors that affect the quality of public services in population administration in Kecamatan Biringkanaya. The study uses a qualitative approach with a case study design. Data were collected through in-depth interviews with key informants and document analysis. The results show that the quality of public services in population administration is influenced by various factors, including human resources, facilities and infrastructure, and regulations. The study also found that local governments have implemented several strategies to improve the quality of public services, such as recruitment and training of qualified human resources, improvement of facilities and infrastructure, and simplification of regulations. In conclusion, this research suggests that local governments need to continue their efforts to improve the quality of public services in population administration by addressing the complex factors that affect it